Impact of sex on outcomes of bifurcation lesion percutaneous coronary intervention: results from a single-centre prospective registry. Issue 1 (January 2022) - Schamroth Pravda, Nili; Perl, Leor; Greenberg, Gabriel; Codner, Pablo; Assali, Abid; Samara, Abed; Porter, Avital; Kornowski, Ran; Vaknin-Assa, Hana
Abstract : Background: Coronary bifurcation lesions are technically and clinically more challenging compared to nonbifurcation lesions. Sex-related differences in diagnostic and invasive therapeutic coronary procedures have been described in the literature. Our objective was to assess the impact of sex on outcomes of bifurcation lesion percutaneous coronary intervention (PCI). Methods: Our data were taken from a prospective registry of consecutive patients undergoing PCI for bifurcation lesions at our medical centre between 2004 and 2019. We compared rates of death and major adverse cardiac events (MACE) between men and women at 1 year and 3 years. MACE comprised cardiac death, myocardial infarction, target vessel revascularization or stroke. Results: A total of 1209 patients were included, 948 (78.4%) were male and 261 (21.6%) were female. Women were older (mean age 69.7 ± 11 years vs. 63.1 ± 11 years, P < 0.01), and had more comorbidities than men. Female patients had more angiographically calcified (38.1% vs. 30.1%, P = 0.017) lesions. At 1-year follow up, there was no significant difference of MACE (18.8 vs. 15.2%, P = 0.183) or all-cause mortality (5.7% vs. 3.9%, P = 0.242) between sexes. At 3-year follow up, there was a significantly higher rate of MACE in women (29.1% vs. 22.5%, P = 0.026), this was driven by a significantly higher all-cause mortality (13.8% vs. 6.5%, P < 0.01). Conclusion: Women undergoing bifurcation PCI are older and have more comorbidities than their male counterparts. Intermediate term follow-up outcomes are similar between sexes. Poorer long-term outcomes of women are likely due to baseline higher risk profile.